Selection of Protein Kinase Inhibitors Based on Tumor Tissue Kinase Activity Profiles in Patients with Refractory Solid Malignancies: An Interventional Molecular Profiling Study. (17th July 2018) - Labots, Mariette; Van der Mijn, Johannes C.; Dekker, Henk; Ruijter, Rita; Pham, Thang V.; Van der Vliet, Hans J.; Van der Hoeven, Jacobus J.M.; Meijer, Gerrit A.; Verheul, Henk M.W.
Abstract: Lessons Learned: Clinically applicable tools are needed for treatment selection and repurposing of available protein kinase inhibitors (PKIs) in patients with advanced solid tumors refractory to standard treatment. Using a tyrosine kinase peptide substrate microarray, observed inhibitory activity in vitro could not sufficiently predict clinical benefit of treatment with the selected PKI. Background: This exploratory molecular profiling study determined the feasibility and benefit of the selection of protein kinase inhibitors (PKIs) based on kinase activity profiling in patients with refractory solid malignancies. Methods: Adult patients with biopsy‐accessible refractory solid tumors were eligible. Per patient, the inhibitory potency of sunitinib, dasatinib, erlotinib, sorafenib, everolimus, and lapatinib was determined in tumor lysates from fresh biopsies using a tyrosine kinase peptide substrate microarray. The most active PKI in this in vitro assay was selected for treatment. Results: Thirteen patients were enrolled in the feasibility part and underwent tumor biopsy. Of 12 patients in whom kinase activity profiling was performed, 11 started treatment with a selected PKI: dasatinib in 8, sunitinib in 2, and erlotinib in 1 patient(s). Eight patients were evaluable for response. One patient had stable disease (SD) >4 months on sunitinib; one patient had SD at 6 weeks but progressive disease (PD) at 12 weeks. The remaining patients had PD after 6 weeks of treatment. Conclusion: Kinase inhibition profiles of multiple PKIs can be reliably determined using fresh tumor biopsies from patients with refractory solid tumors. However, the current in vitro microarray selection approach insufficiently predicted clinical benefit of PKI treatment in these patients.